2017
DOI: 10.3389/fpls.2017.01837
|View full text |Cite
|
Sign up to set email alerts
|

Invader Competition with Local Competitors: Displacement or Coexistence among the Invasive Khapra Beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae), and Two Other Major Stored-Grain Beetles?

Abstract: Local potential competitor species are important determinants of the invasibility of an environment even when widely recognized invasive species are concerned since it may compromise its establishment. Thus, the outcome of the direct competition among the invasive khapra beetle, Trogoderma granarium, and the cosmopolitan species lesser grain borer, Rhyzopertha dominica and rice weevil, Sitophilus oryzae, and thus the likelihood of establishment of T. granarium under their co-occurrence, was here explored in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 57 publications
1
50
0
Order By: Relevance
“…Increased fecundity in the presence of competition, although usually unexpected, has been observed in other studies. For example, Kavallieratos et al () found that the population growth of the khapra beetle Trogoderma granarium (Everts) was favored by the presence of two other competitor species, particularly in high temperatures. Sakka & Athanassiou () observed that in some particular conditions (concerning host species and temperature), the progeny production of Dinoderus porcellus (Lesne) was increased in the presence of two other competing beetle species, the bostrychids Rhyzopertha dominica (Fabricius) and Prostephanus truncatus (Horn).…”
Section: Discussionmentioning
confidence: 99%
“…Increased fecundity in the presence of competition, although usually unexpected, has been observed in other studies. For example, Kavallieratos et al () found that the population growth of the khapra beetle Trogoderma granarium (Everts) was favored by the presence of two other competitor species, particularly in high temperatures. Sakka & Athanassiou () observed that in some particular conditions (concerning host species and temperature), the progeny production of Dinoderus porcellus (Lesne) was increased in the presence of two other competing beetle species, the bostrychids Rhyzopertha dominica (Fabricius) and Prostephanus truncatus (Horn).…”
Section: Discussionmentioning
confidence: 99%
“…Resource competition is a common biotic factor that may affect the population outcome among living organisms (Le Bourlot et al, 2014;Pedruski et al, 2015). It may affect several biological features, such as population size of herbivorous species (Karban, 1986;Athanassiou et al, 2014Athanassiou et al, , 2017aKavallieratos et al, 2017b), progeny production, fitness and prey consumption of beneficial insects (Xu et al, 2013;Cusumano et al, 2016;Papanikolaou et al, 2016). In addition, direct or indirect competitive interactions between species may lead to displacement of established species from a habitat (Reitz and Trumble, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For example, insects, mainly coleopterans, are responsible for huge grain losses of up to 57% in Africa (Kumar and Kalita 2017). Several stored-product coleopterous species co-exist in storage facilities and consequently compete for the same food resources (Smith and Lessells, 1985;Smith, 1990Smith, , 1991Athanassiou et al, 2003Athanassiou et al, , 2005Athanassiou et al, , 2011Athanassiou et al, , 2017aKavallieratos et al, 2017b). Although competition is considered a serious issue in storage ecosystem (Smith and Lessells, 1985;Smith, 1990Smith, , 1991Kavallieratos et al, 2017b) there is a gap of knowledge regarding interspecific competition.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations